Benign hepatocellular nodules of healthy liver: focal nodular hyperplasia and hepatocellular adenoma - Roncalli, Massimo (Clin Mol Hepatol, 2016)
Owing to the progress of imaging techniques, benign hepatocellular nodules are increasingly discovered in the clinical practice. This group of lesions mostly arises in the context of a putatively normal healthy liver and includes either pseudotumoral and tumoral nodules. Focal nodular hyperplasia and hepatocellular adenoma are prototypical examples of these two categories of nodules. In this review we aim to report the main pathological criteria of differential diagnosis between focal nodular hyperplasia and hepatocellular adenoma, which mainly rests upon morphological and phenotypical features. We also emphasize that for a correct diagnosis the clinical context such as sex, age, assumption of oral contraceptives, associated metabolic or vascular disturbances is of paramount importance. While focal nodular hyperplasia is a single entity epidemiologically more frequent than adenoma, the latter is representative of a more heterogeneous group which has been recently and extensively characterized from a clinical, morphological, phenotypical and molecular profile. The use of the liver biopsy in addition to imaging and the clinical context are important diagnostic tools of these lesions. In this review we will survey their systematic pathobiology and propose a diagnostic algorithm helpful to increase the diagnostic accuracy of not dedicated liver pathologists. The differential diagnosis between so-called typical and atypical adenoma and well differentiated hepatocellular carcinoma will also be discussed.